Transdiagnostic emotion-focused therapy : a clinical guide for transforming emotional pain - Timulak, Ladislav; Keogh, Daragh (American Psychological Association, 2022)
"Emotion-Focused Therapy is an effective transdiagnostic treatment for the common symptoms that underlie depression, anxiety, and other related disorders. Given the high comorbidity of mental health symptoms and our growing understanding of psychopathology, transdiagnostic treatments are becoming more and more common. This book conceptualizes Emotion-Focused Therapy (EFT) as a transdiagnostic approach for treating a variety of mental health problems. The authors use elements of a modular approach that is the culmination of a decade-long research program, targeting some symptom-level presentations, as well as the underlying emotional vulnerability that manifests in depression, anxiety, and other related disorders. This approach conceptualizes and integrates a range of symptom-level EFT tasks, including tasks aimed at facilitating regulation of emotional distress, as well as tasks that specifically target self-worrying, rumination, perfectionism, and other discrete symptoms. Strategies that target clusters of symptoms, such as two-chair dialogues and self-interruption, are illustrated through richly detailed session transcripts. This book helps mental health professionals enable their clients to access emotional vulnerability, facilitate emotional regulation, guide emotional transformation processes, and engage in healthy interpersonal experiences"--